Malnutrition and epidemics are intertwined: That makes fixing food systems crucial - Gillespie, Stuart (2020)
Malnutrition is by far the biggest driver of ill-health and premature mortality in every region of the world. A slow-burn attritional problem, it does enormous damage. The COVID-19 epidemic that’s sweeping the world, meanwhile, brings a series of massive short-wave shocks. Both the epidemic and malnutrition will generate long-wave impacts, for years to come. They are also likely to interact with each other – badly. This will be particularly true in countries in sub-Saharan Africa and South Asia. Many of these countries’ governments, health and food systems, communities and households have limited capacity to respond to nutritional challenges or to an epidemic. This means that the potential exists for malnutrition to exacerbate the health consequences of the COVID-19 epidemic, and vice versa.